Channel modeling and bit error rate performance for fixed broadband wireless access [electronic resource] - 372497 Khaled Mohamed Ramadan Sofrani; Tharek Abd. Rahman, supervisor (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunakasi)) - Universiti Teknologi Malaysia, 2008